Clinical and molecular characterization of early‐onset colorectal cancer. Issue 12 (11th March 2019) - Willauer, Alexandra N.; Liu, Yusha; Pereira, Allan A. L.; Lam, Michael; Morris, Jeffrey S.; Raghav, Kanwal P. S.; Morris, Van K.; Menter, David; Broaddus, Russell; Meric‐Bernstam, Funda; Hayes‐Jordan, Andrea; Huh, Winston; et al.
Abstract : Background: Colorectal cancer (CRC) incidence is increasing in adults younger than 50 years. This study evaluated clinical and molecular features to identify those features unique to early‐onset CRC that differentiate these patients from patients 50 years old or older. Methods: Baseline characteristics were evaluated according to the CRC onset age with 3 independent cohorts. A fourth cohort was used to describe the impact of age on the consensus molecular subtype (CMS) prevalence. Results: This retrospective review of more than 36, 000 patients with CRC showed that early‐onset patients were more likely to have microsatellite instability ( P  = .038), synchronous metastatic disease ( P  = .009), primary tumors in the distal colon or rectum ( P  < .0001), and fewer BRAF V600 mutations ( P  < .001) in comparison with patients 50 years old or older. Patients aged 18 to 29 years had fewer adenomatous polyposis coli (APC) mutations (odds ratio [OR], 0.56; 95% confidence interval [CI], 0.35‐0.90; P  = .015) and an increased prevalence of signet ring histology (OR, 4.89; 95% CI, 3.23‐7.39; P  < .0001) in comparison with other patients younger than 50 years. In patients younger than 40 years, CMS1 was the most common subtype, whereas CMS3 and CMS4 were uncommon ( P  = .003). CMS2 was relatively stable across age groups. Early‐onset patients with inflammatory bowel disease were more likely to have mucinous or signet ring histology (OR, 5.54; 95% CI, 2.24‐13.74; P  = .0004) and less likely to have APC mutations (OR, 0.24; 95% CI, 0.07‐0.75; P  = .019) in comparison with early‐onset patients without predisposing conditions. Conclusions: Early‐onset CRC is not only distinct from traditional CRC: special consideration should be given to and further investigations should be performed for both very young patients with CRC (18‐29 years) and those with predisposing conditions. The etiology of the high rate of CMS1 in patients younger than 40 years deserves further exploration. Abstract : Early‐onset colorectal cancer (at an age <50 years) has distinct clinical and molecular features, including increased prevalences of synchronous metastatic disease, microsatellite instability, primary tumors located in the distal colon or rectum, and consensus molecular subtype 1 and fewer mutations in BRAF V600, in comparison with colorectal cancer in patients older than 50 years. Among patients with early‐onset colorectal cancer, those aged 18 to 29 years and those with predisposing conditions are distinct from the other patients younger than 50 years, and this suggests that considering all patients with colorectal cancer younger than 50 years together may not be appropriate.